The labor demand was downward sloping: Disentangling migrants' inflows and outflows, 1929 - 1957 - Costanza Biavaschi (Institute for the Study of Labor (IZA), 2012)
This paper studies in- and out-migration from the U.S. during the first half of the twentieth century and assesses how these flows affected state-level labor markets. It shows that out-migration positively impacted the wages of remaining workers, while in-migration had a negative impact. Hence, immigrant arrivals were substitutes of the existing workforce, while out-migration reduced the competitive pressure on labor markets.
Keywords: F22; J01; J61; N32; 330; migration flows; impact of migration; Einwanderung; Auswanderung; Arbeitsmarkt; Lohn; Teilstaat; USA